Genetic parameters for buffalo milk yield and milk quality traits using animal model - Ibrahim, M. A.; Khattab, A. S.; El-Habaeib, Set; Awad, S.; Tőzsér, J. (Animal Welfare, Etológia és Tartástechnológia (AWETH), 2012)
A total of 365 normal first lactation records of Egyptian buffaloes, kept at Mehalet Mousa Farm, belonging to the Animal Production Research Institute, Ministry of Agriculture, Dokki Cairo, Egypt, during the period from 2001 to 2006 were used. Data were analyzed by using Statistical Analysis System (SAS) to study the fixed effects of month and year of calving and random effect of sire on milk yield (MY), lactation period (LP), fat yield (FY), protein yield (PY) and somatic cell count (SCC). In addition, genetic parameters (i.e., heritability, genetic correlation and phenotypic correlation) among different traits studied were analysed by using Multi Trait Animal model (MTAM). Means for MY, LP, FY, PY, and SCC were 1536 kg, 198.84 d, 147.67 kg, 81.21 kg and 156.21, respectively. Month and year of calving of had a significant effect on MY, LP, FY and PY, while month of calving had no significant effect on SCC. Sire of the heifers had a significant effect on all traits studied, expect the effect of sire on SCC. Heritability estimates (±SE) for MY, LP, FY, PY and SCC were 0.40± 0.07, 0.30 ± 0.06, 0.19 ± 0.04, 0.22 ± 0.05 and 0.05± 0.09, respectively. Estimates of genetic correlations (rg) between milk traits (i.e., MY, LP, FY and PY), were positive and highly significant and ranged from 0.18 (0.10) to 0.75 (0.07), while the genetic correlation between SCC and all milk traits were negative and ranged from – 0.18 (0.10) to – 0.40 (0.21). Phenotypic correlations (rp) among all traits studied are in the same direction of genetic correlations.